2011
DOI: 10.1111/j.1654-1103.2011.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of plant community assembly in invaded and non‐invaded communities along a natural environmental gradient

Abstract: Questions: Is the stress gradient hypothesis (SGH) effective in predicting\ud patterns of community assembly in coastal dune plant communities along the\ud sea–inland environmental gradient? Does the introduction of invasive plant species\ud disrupt these patterns, leading to a collapse in community structure?\ud Location: Sandy coastal dunes of the Lazio region (Central Italy).\ud Methods:We randomly sampled coastal dune plant species in 2 m 9 2 mplots\ud (4 m2). Multivariate techniques were used to classify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 75 publications
(181 reference statements)
3
61
1
Order By: Relevance
“…Most of the existing studies regarding the effect of invasive plants on biodiversity focus solely on the number of species as a measure of biodiversity ignoring other indicators of biodiversity which are more closely related to ecosystem functioning, such as the diversity of evolutionary histories or phylogenetic diversity (Forest et al 2007;Maherali and Klironomos 2007; see also Santoro et al 2012;Hejda and de Bello 2013;Bennett et al 2014). Numerous important ecological traits, such as co-evolved relationships with N-fixing bacteria or other soil organisms, are preserved through evolutionary times (Flynn et al 2011;Milcu et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Most of the existing studies regarding the effect of invasive plants on biodiversity focus solely on the number of species as a measure of biodiversity ignoring other indicators of biodiversity which are more closely related to ecosystem functioning, such as the diversity of evolutionary histories or phylogenetic diversity (Forest et al 2007;Maherali and Klironomos 2007; see also Santoro et al 2012;Hejda and de Bello 2013;Bennett et al 2014). Numerous important ecological traits, such as co-evolved relationships with N-fixing bacteria or other soil organisms, are preserved through evolutionary times (Flynn et al 2011;Milcu et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Coastal ecosystems are regarded as threatened by alien invasion worldwide (McLachlan and Brown 2006;Santoro et al 2012). Their high sensitivity to alien establishment seems to be related to natural and anthropogenic factors such as habitat heterogeneity, intensive propagule pressure from ancient times, and frequent and diverse disturbances (Acosta et al 2007(Acosta et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, regarding our second hypothesis, although F. foetida plants showed significant increase in cover and number of leaves over the one-year period of the study no difference was found for native species richness, diversity, and cover between invaded and uninvaded plots. Other authors have showed that species richness remained stable in invaded and uninvaded plots by different invasive plant species although some of them only displaced the dominant native species and had no effects on non-dominant species (Sax, 2002;Mason and French, 2008;Powell et al, 2013;Dong et al, 2015). Hejda et al (2009) found that decreases in species richness in invaded plots by different invasive plant species significantly interacted with species-specific differences in cover between the invading and native dominant species.…”
Section: Discussionmentioning
confidence: 99%
“…Propagules may also arrive on coastal dunes from the ocean especially with high tides (Aptekar and Rejmánek, 2000). Non-native invasive species impacts on costal dune ecosystems include native species displacement, decreasing soil stabilization functions (Kim, 2005), competition for resources (Santoro et al, 2012), and native species richness or diversity decline (Badano and Pugnaire, 2004;Carboni et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation